Communion : the female search for love - hooks, bell, 1952-2021 (William Morrow, 2003)
Renowned visionary and theorist bell hooks began her exploration of the meaning of love in American culture with the critically acclaimed All About Love: New Visions. She continued her national dialogue with the bestselling Salvation: Black People and Love. Now hooks culminates her triumphant trilogy of love with Communion: The Female Search for Love. Intimate, revealing, provocative, Communion challenges every female to courageously claim the search for love as the heroic journey we must all choose to be truly free. In her trademark commanding and lucid language, hooks explores the ways ideas about women and love were changed by feminist movement, by women's full participation in the workforce, and by the culture of self-help. Communion is the heart-to-heart talk every woman -- mother, daughter, friend, and lover -- needs to have.